Tingkat Partisipasi Olahraga Mahasiswa Baru Fakultas Ilmu Keolahragaan: Ipa Sari Kardi - Kardi, Ipa Sari (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
A degree of health and physical fitness is obtained by actively exercising. The more regularly you exercise, the fitter you will be and vice versa. The less exercise, the risk of hypokinetic disease. The purpose of this study was to determine the level of sports participation of new students of the FIK UNCEN Sports Science Study Programme class of 2023. Using quantitative research with descriptive methods to draw the level of student sports participation. The sampling technique uses total sampling, namely the entire population of 88 new students. The data collection technique uses an index of participation in sports, namely a questionnaire that has been valid and reliable for use with a Conbach's alpha value of 0.934. The questionnaire consists of 24 positive statement items and 16 negative question items. The data analysis technique used descriptive analysis using spss. 29. The results of the study found that the sports participation index of new students of the Sports Science Study Program of FIK UNCEN in terms of the dominant need aspect of the high category 44.3%, the dominant benefit aspect of the high category 43.2%, and the dominant attitude aspect of the 48.9% category. Based on the results of data analysis, it is concluded that the level of sports participation of new students of the FIK UNCEN Sports Science Study Program is dominant in the high category, although there are several sub-indicators that are still in the low category. Therefore, it is expected that FIK Cenderawasih University students increase their participation in sports activities by being active and involved in sports UKM or joining certain sports clubs. This is in addition to improving health status and supporting Papua as a sports province